2021
DOI: 10.3390/met11111775
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Dislocations and Penta-Twins in Metallic Nanocrystals

Abstract: Dislocation interactions with twin boundary (TB) have been well-established in nanotwinned metals. Penta-twins, as an extreme of crystal twinning, are tacitly assumed to be more effective at blocking dislocation motions than conventional single or coplanar nanotwins. However, the mechanism underlying the interactions between dislocations and penta-twins remains largely unclear. Here, by combining in situ transmission electron microscope (TEM) nanomechanical testing and atomistic simulations, we rationalize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Twin boundaries (TBs) with low mobility and boundary energy can be used for tuning the mechanical properties of nanostructured metals, 1 , 2 which have drawn great interest in the field of interface engineering. 3 , 4 As a special twinning morphology, a 5-fold twin (FFT) with five coherent TBs concurrently meeting at their common rotation axis along [110] has been widely observed in metallic nanowires, 5 7 nanoparticles, 8 , 9 thin films, 10 and nanocrystalline materials. 11 13 Compared to their twin-free counterparts, the nanostructured metals with FFT usually exhibit substantially improved mechanical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twin boundaries (TBs) with low mobility and boundary energy can be used for tuning the mechanical properties of nanostructured metals, 1 , 2 which have drawn great interest in the field of interface engineering. 3 , 4 As a special twinning morphology, a 5-fold twin (FFT) with five coherent TBs concurrently meeting at their common rotation axis along [110] has been widely observed in metallic nanowires, 5 7 nanoparticles, 8 , 9 thin films, 10 and nanocrystalline materials. 11 13 Compared to their twin-free counterparts, the nanostructured metals with FFT usually exhibit substantially improved mechanical properties.…”
mentioning
confidence: 99%
“…Twin boundaries (TBs) with low mobility and boundary energy can be used for tuning the mechanical properties of nanostructured metals, , which have drawn great interest in the field of interface engineering. , As a special twinning morphology, a 5-fold twin (FFT) with five coherent TBs concurrently meeting at their common rotation axis along [110] has been widely observed in metallic nanowires, nanoparticles, , thin films, and nanocrystalline materials. Compared to their twin-free counterparts, the nanostructured metals with FFT usually exhibit substantially improved mechanical properties. It has been reported that the Young’s modulus of chemically synthesized pentatwinned silver (Ag) nanowires increased from 83 to 176 GPa , and the yield strength increased from 0.71 to 2.64 GPa . Controlling the introduction of FFT into nanostructured metals is of vital importance for fabricating high-performance materials, which requires the knowledge of the underlying formation mechanisms of FFT.…”
mentioning
confidence: 99%